Mistycyzm buddyzmu tybetańskiego – charakterystyka Drogi Wglądu - Wysocki, Adam (Kultura-Społeczeństwo-Edukacja, 2020)
Wysocki Adam, Mysticism in Tibetan Buddhism. A study into the Path of Insight. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 183–201, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.12. The Path of Insight is a spiritual path of Tibetan Buddhism tradition. The fundamental part consists of three elements, such like: preliminary practices, the tranquility meditation and the penetrating insight meditation. However, counted three parts one ought to perceive as aspects of one process aiming to realize of the soteriology purpose. The achievement of the non-dual state has its own development process, which consists experience of the non-dual state, stabilise it and then development of it. Outline of development process is contained in the Path o Insight and relies on exceeding of subjective-objective divisibility. It is perceived as an effect of the ignorance of true nature of the individual. The achievement of the non-dual state, that is nature of the mind (tib. sems nyid) constitutes the purpose of the Path of Insight and it is described by concept-symbol called mahamudra.